The Territorial Distribution of Public Health and Social-Sanitary Resources for the Major Population - Ana Nieto-Masot; Ángela Engelmo-Moriche; Gema Cárdenas-Alonso (Revista de Estudios Andaluces, 2019)
Extremadura is a region with significant demographic imbalances, especially with high aging rates. Its older population demands resources and equipments and, therefore, the objective of this work is to analyse whether the supply of health and social-health resources of a public nature presents an adequate distribution. Methodologically, Geographical Information Systems are used to calculate the accessibility to health resources and equipment and spatial correlation to determine if there are concentrations, as well as if they are related to the demand due to high aging. In response to the results obtained, as the concentration of negative contexts in the most rural areas, a series of improvements are established in order to contribute to greater social justice in Extremadura.